2015
DOI: 10.5433/1679-0359.2015v36n5p2987
|View full text |Cite
|
Sign up to set email alerts
|

Germinação e crescimento de plântulas de genótipos de aveia branca submetidas ao estresse salino

Abstract: <p>A aveia branca é uma cultura de inverno utilizada em sucessão ao cultivo do arroz irrigado, estando sujeita ao estresse salino, devido ao acúmulo de sais no solo, principalmente na região sul do Rio Grande do Sul. O objetivo deste trabalho foi avaliar a germinação de sementes, o crescimento inicial das plântulas de nove genótipos de aveia branca, bem como identificar os genótipos contrastantes para o caráter tolerância à salinidade. Para isso, os genótipos foram submetidos a diferentes concentrações s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A reduction in the GSI under saline stress in association with an osmotic potential ranging from 0.0 MPa to 1.2 MPa has been reported by other authors working with several species of agronomic interest, such as soybean (Chichanosk et al, 2019), sunflower (Rossetto et al, 2021), and oat (Timm et al, 2015). According to Leal et al (2020), this is because low osmotic potentials reduce the absorption of water by seeds and can prevent the sequence of events in the germination process from occurring, thereby reducing the germination speed and percentage.…”
Section: Resultsmentioning
confidence: 54%
“…A reduction in the GSI under saline stress in association with an osmotic potential ranging from 0.0 MPa to 1.2 MPa has been reported by other authors working with several species of agronomic interest, such as soybean (Chichanosk et al, 2019), sunflower (Rossetto et al, 2021), and oat (Timm et al, 2015). According to Leal et al (2020), this is because low osmotic potentials reduce the absorption of water by seeds and can prevent the sequence of events in the germination process from occurring, thereby reducing the germination speed and percentage.…”
Section: Resultsmentioning
confidence: 54%
“…Silva et al (2020) observed that the chemical composition of the BRS Zuri cultivar of Megathyrsus maximus is negatively affected by increasing salinity levels, with a 9.46% reduction in crude protein (CP) content and a 1.34% increase in neutral detergent fiber (NDF). Timm et al (2015) observed a decrease of about 5.0% in seedling emergence percentage and 21.7% in the emergence speed index with increasing salt stress in all white oat (Avena sativa L.) cultivars, while in forage sorghum (Sorghum bicolor L. Moench), Coelho et al (2014) found no differences in seedling emergence percentage among the cultivars evaluated. Although studies evaluating these parameters in M. maximus are scarce, it was observed that increasing irrigation with saline water causes damage to the percentage and speed of germination, as well as to the chemical composition of forage cultivars.…”
Section: Resultsmentioning
confidence: 88%
“…In the present study, statistically differentiated behavior among cultivars for parameters related to seedling emergence was not observed at the salinity levels employed. Several studies have been conducted with other grass species, and the results show variation in the effect of salt stress among different species and cultivars (Coelho et al, 2014;Timm et al, 2015;Silva et al, 2020). Silva et al (2020) observed that the chemical composition of the BRS Zuri cultivar of Megathyrsus maximus is negatively affected by increasing salinity levels, with a 9.46% reduction in crude protein (CP) content and a 1.34% increase in neutral detergent fiber (NDF).…”
Section: Resultsmentioning
confidence: 99%